2010
DOI: 10.1007/s00405-010-1245-8
|View full text |Cite
|
Sign up to set email alerts
|

Nasal mucosal contact points with facial pain and/or headache: lidocaine can predict the result of localized endoscopic resection

Abstract: The objective of the study was conducted to evaluate the effectiveness of nasal endoscopy for both diagnosis and localized excision of intranasal contact areas that cause headache and/or facial pain as well as to evaluate the use of lidocaine test for diagnosis of such cases and predicting the result of surgery. This study included 120 patients aged between 18 and 45 years, with an average period of headache and/or facial pain of 2.5 years. Patients were classified into two groups according to lidocaine test. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 13 publications
0
11
0
2
Order By: Relevance
“…Performing a "topical anesthesia test" before surgery thereby enabled the authors to select children who reported an improvement. Nevertheless, this test did not guarantee the selection of those patients who would benefit from surgery, as reported by different authors [31][32][33]. However, none of these authors has found a distinct correlation between a positive test result and a surgical outcome.…”
Section: Discussionmentioning
confidence: 72%
“…Performing a "topical anesthesia test" before surgery thereby enabled the authors to select children who reported an improvement. Nevertheless, this test did not guarantee the selection of those patients who would benefit from surgery, as reported by different authors [31][32][33]. However, none of these authors has found a distinct correlation between a positive test result and a surgical outcome.…”
Section: Discussionmentioning
confidence: 72%
“…In spite of the low level of evidence, selected patients with mucosal contact points who appear to benefit from directed nasal surgery are those who have failed medical therapy for migraine and tension‐type headache, have otherwise normal endoscopy and CT scan, and have symptomatic improvement with local anesthetic application to the contact point in preoperative evaluation . However, it is not clear why a significant proportion of patients have residual symptoms after surgery . In addition, several studies claimed good response to surgical treatment in patients with less strict selection criteria.…”
Section: Discussionmentioning
confidence: 99%
“…A false‐positive test may be seen in some migraineurs due to resolution of allodynia or neuroplasticity . To further confound the above‐mentioned selection criteria, some patients still benefit from surgery with a negative lidocaine test, although responders were found to have better outcome …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations